“Chinese Students Themselves Are Changing”: Why We Need Alternative Perspectives of Chinese International Students - Heng, Tang Tang (Journal of International Students, 2020)
Given how China has been the top source of international students worldwide, there has been growing media and research interest in Chinese international students. However, much of the narratives tend to focus on their struggles. In this commentary, I draw upon insights from my personal experience as an international student and, consequently, research on Chinese international students to illuminate alternative ways of understanding Chinese internationals and the reasons for why these perspectives around international students are necessary.